2016
DOI: 10.3847/0004-637x/822/2/81
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Rapidly Rotating M Dwarfs in the Pleiades So (Infra)red? New Period Measurements Confirm Rotation-Dependent Color Offsets From the Cluster Sequence

Abstract: Stellar rotation periods (P rot ) measured in open clusters have proved to be extremely useful for studying stars' angular momentum content and rotationally driven magnetic activity, which are both age-and mass-dependent processes. While P rot measurements have been obtained for hundreds of solar-mass members of the Pleiades, measurements exist for only a few low-mass (<0.5 M ) members of this key laboratory for stellar evolution theory. To fill this gap, we report P rot for 132 low-mass Pleiades members (incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 72 publications
(114 reference statements)
8
51
1
Order By: Relevance
“…This hypothesis is supported by the work of Kamai et al (2014): these authors found a positive correlation between rotation rate and color abnormality, suggesting that the most rapidly rotating, and thus perhaps the most heavily spotted stars, show the greatest abnormalities. A rotation-color correlation was later demonstrated for the stars less massive than spectral-type K by Covey et al (2016). Moreover, Somers & Stassun (2017) found a connection between rotation rate and radius inflation within this cluster, signifying that magnetic activity is likely influencing the structure of these K-dwarfs.…”
Section: The K-dwarfs Of the Pleiadesmentioning
confidence: 82%
“…This hypothesis is supported by the work of Kamai et al (2014): these authors found a positive correlation between rotation rate and color abnormality, suggesting that the most rapidly rotating, and thus perhaps the most heavily spotted stars, show the greatest abnormalities. A rotation-color correlation was later demonstrated for the stars less massive than spectral-type K by Covey et al (2016). Moreover, Somers & Stassun (2017) found a connection between rotation rate and radius inflation within this cluster, signifying that magnetic activity is likely influencing the structure of these K-dwarfs.…”
Section: The K-dwarfs Of the Pleiadesmentioning
confidence: 82%
“…For example, anomalous colors of K dwarfs in the Pleiades can be explained by ∼50% fill factors of spots (Stauffer et al 2003), while LAMOST spectra of the TiO band indicates that ∼ 30% spot coverages may be common for 3500-5000 K stars (Fang et al 2016). Recent photometric monitoring of the Pleiades indicates that the anomalous colors scale with rotation rate, strengthing the case for magnetic-field induced starspots as the cause of the anomaly (Covey et al 2016). However, the Covey et al (2016) Pleiades rotation rates do not scale with the ∆V photometric amplitude at the precision of the PTF data, suggesting that while the overall starspot coverage increases with rotation rate, the longitudinally asymmetric component does not.…”
Section: Discussionmentioning
confidence: 99%
“…Recent photometric monitoring of the Pleiades indicates that the anomalous colors scale with rotation rate, strengthing the case for magnetic-field induced starspots as the cause of the anomaly (Covey et al 2016). However, the Covey et al (2016) Pleiades rotation rates do not scale with the ∆V photometric amplitude at the precision of the PTF data, suggesting that while the overall starspot coverage increases with rotation rate, the longitudinally asymmetric component does not. LkCa 4 represents an example of such an architecture, with more than 50% of the visible stellar surface covered in spots at all observational phases.…”
Section: Discussionmentioning
confidence: 99%
“…Hartman et al (2011) measure a period of 11.2days for 2M2236+4751; compared to the Pleaides rotation distribution, which has a comparable age to AB Dor and a well characterized stellar population, this period sits near the maximum envelope of rotation rates for stellar masses of ≈0.6M e (Hartman et al 2010;Covey et al 2016;Rebull et al 2016). K7 members in AB Dor exhibit a similarly broad range of rotation periods from 0.4-9.3 days (Table 3).…”
Section: Age and Young Moving Group Membershipmentioning
confidence: 99%